ANTIBACTERIAL, ANTIOXIDANT, CHEMICAL CONSTITUENTS, AND CYTOTOXICITY EVALUATION OF TERMINALIA ARJUNA (ROXB. EX DC.) WIGHT AND ARN - Khatri, Savita; Phougat, Neetu; Dangi, Mehak; Chhillar, Anil Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The objective of this study is to evaluate the in vitro antibacterial and antioxidant prospective of Terminalia arjuna (leaves). The most active extracts were examined for their chemical composition and cytotoxicity. Methods: The antibacterial activity of five different extracts were examined against 8 bacterial strains (5 Gram-positive and 3 Gram-negative) using resazurin-based microtiter dilution assay (RMDA) and disk-diffusion assay. The antioxidant potential of five extracts was demonstrated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay and superoxide radical scavenging assay. Chemical composition and cytotoxicity were assessed using gas chromatography-mass spectrometry (GC-MS) and hemolytic assay, respectively. Results: According to RMDA, the acetone extract (AE) exhibited highest antibacterial activity. The AE showed highest activity against Salmonella enterica ser. typhi and Bacillus cereus with minimum inhibitory concentration, i.e., 195.31 Î¼g/ml. In DPPH assay, AE showed the highest radical scavenging activity with inhibition concentration50 23.09 Î¼g/ml. In GC-MS analysis, the principal compound in AE was celidoniol (8.72 %). According to the results of hemolytic assay, the AE showed non-toxic behavior upto 500 Î¼g/ml. Conclusion: The present investigation represents T. arjuna as an incredible herb. The AE was found to possess promising antibacterial and antioxidant properties. Keywords: Antibacterial, Antioxidant, Terminalia arjuna, Chemical composition, Cytotoxicity.